1997
DOI: 10.1093/carcin/18.9.1763
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking induces an increase in oxidative DNA damage, 8- hydroxydeoxyguanosine, in a central site of the human lung

Abstract: To evaluate the effect of cigarette smoking on oxidative stress in lung tissues, we compared the levels of a type of oxidative DNA damage, 8-hydroxydeoxyguanosine (8-OH-dG), in tissue obtained from the central sites of lungs from 14 current smokers, seven ex-smokers and nine non-smokers. The mean level of 8-OH-dG in the lung tissues from smokers was 1.43-fold higher than that of the non-smokers (the difference was statistically significant, P = 0.0262). A positive correlation between the 8-OH-dG levels in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
137
2
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(149 citation statements)
references
References 12 publications
8
137
2
2
Order By: Relevance
“…This result is in agreement with others in the literature [16,39], indicating that cigarette smoking induces oxidative damage to DNA, although the effect was not observed in all smokers.…”
Section: Analysis Of Urinary 8ohdg and Study Of The Association With supporting
confidence: 93%
See 3 more Smart Citations
“…This result is in agreement with others in the literature [16,39], indicating that cigarette smoking induces oxidative damage to DNA, although the effect was not observed in all smokers.…”
Section: Analysis Of Urinary 8ohdg and Study Of The Association With supporting
confidence: 93%
“…Loft et al [9] reported smokers excreted 50% more 8OHdG than non-smokers in 24 h urine, indicating a 50% increased rate of oxidative DNA damage from smoking. Asami et al [16] found a positive correlation between the number of cigarette smoked per day and the 8OHdG levels in normal lung tissues. But there are overall very few data on oxidative DNA damage in smokers.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…These different reactive species might be responsible for much of the tissue injuries and disease states associated with inflammation. Increased oxidative DNA damage, such as 8-hydroxyguanine formation in human lung tissue [5], is found in smokers compared with non-smokers. Oxidative stress may play an important role in the pathogenesis of smoking-associated diseases, such as chronic obstructive pulmonary diseases (COPD) [6,7], asthma [8], and carcinogenesis [9-11].…”
Section: Introductionmentioning
confidence: 99%